2017
DOI: 10.1038/s41598-017-15972-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inducible factor-1α mediates the profibrotic effect of albumin in renal tubular cells

Abstract: Proteinuria is closely associated with the progression of chronic kidney diseases (CKD) by producing renal tubulointerstitial fibrosis. Over-activation of hypoxia inducible factor (HIF)-1α has been implicated in the progression of CKD. The present study tested the hypothesis that HIF-1α mediates albumin-induced profibrotic effect in cultured renal proximal tubular cells. Incubation of the cells with albumin (40 μg/ml) for 72 hrs significantly increased the protein levels of HIF-1α, tissue inhibitor of metallop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…Fibrosis causes microvasculature injury and inflammatory stimulation decreases oxygen permeation and increases renal tubular epithelial cells metabolism, which can lead to the persistent hypoxic condition of renal tissue. Conversely, hypoxia can trigger the apoptosis of renal tubular epithelial cells and stimulate the phenotype transformation from renal tubular cells to myofibroblasts (Hu et al, 2017;Liu et al, 2018;Shu et al, 2019). Hypoxia could also promote the expression of tissue inhibitors of metalloproteinases (TIMPS), which would inhibit the degradation of ECM, reduce the blood flow of capillaries around renal tubules and damage the diffusion of oxygen, thus aggravating the local hypoxia (Volker, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis causes microvasculature injury and inflammatory stimulation decreases oxygen permeation and increases renal tubular epithelial cells metabolism, which can lead to the persistent hypoxic condition of renal tissue. Conversely, hypoxia can trigger the apoptosis of renal tubular epithelial cells and stimulate the phenotype transformation from renal tubular cells to myofibroblasts (Hu et al, 2017;Liu et al, 2018;Shu et al, 2019). Hypoxia could also promote the expression of tissue inhibitors of metalloproteinases (TIMPS), which would inhibit the degradation of ECM, reduce the blood flow of capillaries around renal tubules and damage the diffusion of oxygen, thus aggravating the local hypoxia (Volker, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that the expression of NEAT1 was significantly increased in both HFD-and STZ-induced DM mice and a BSA-induced fibrosis and EMT model in HK-2 cells. It has been reported that proteinuria can promote the progression of renal tubulointerstitial fibrosis and DKD 30,31 . BSA has been reported to induce renal proximal tubular cells to mimic tubulointerstitial fibrosis in vitro 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Proteinuria is the primary feature of DKD and is positively correlated with the progression to end‐stage renal disease (Gross et al, ). It has been reported that the exposure of proximal tubular epithelial cells to excess proteins causes tubulointerstitial fibrosis and the progression of DKD (Allouch & Munusamy, ; Hu et al, ; Jheng et al, ; Nishi et al, ; Wu, He, Jing, Li, & Zhang, ). Furthermore, in the early stage of DKD, the onset of proteinuria causes tubular function and morphological injury (Thomas, Burns, & Cooper, ).…”
Section: Discussionmentioning
confidence: 99%